Bones of Contention: A Comprehensive Literature Review of Non-SSRI Antidepressant Use and Bone Health. (November 2020) - Power, Clodagh; Duffy, Richard; Mahon, James; McCarroll, Kevin; Lawlor, Brian A.
Osteoporotic fractures are associated with major morbidity and mortality, particularly among older age groups. In recent decades, selective serotonin reuptake inhibitors (SSRI) antidepressants have been linked to reduced bone mineral density and increased risk of fragility fracture. However, up to one-third of antidepressant prescriptions are for classes other than SSRIs. Older patients, who are particularly vulnerable to osteoporosis and its clinical and psychosocial consequences, may be prescribed non-SSRI antidepressants preferentially because of increasing awareness of the risks SSRIs pose to bone health. However, to date, the skeletal effects of non-SSRI antidepressants have not been comprehensively reviewed. In this article, we collate and review the available data and discuss the findings. Based on the current literature, we tentatively suggest that tricyclic antidepressants may increase the risk of fracture via mechanisms other than a direct effect on bone mineral density. The risk is apparently confined to current users only and is greatest in the earliest stage of treatment, diminishing thereafter. There is, as yet, insufficient data to conclusively determine the effects of other antidepressant classes on bone. Judicious prescribing of antidepressants among higher risk groups necessitates a thorough review of the individual's risk factors for osteoporosis as well as attention to their falls risk. Further longitudinal, rigorously controlled studies are needed to answer some of the remaining questions on the effects of non-SSRI antidepressants on bone and the mechanisms by which they are exerted.